The Arithmomania Maths App: The glitch that corrupted learning to leave only fun. Issue 1 (2nd January 2018) - Kawka, Marta; Larkin, Kevin
ABSTRACT: In this article we critique, disrupt and resist the taken for granted use of the term fun in learning; specifically as it is used to justify mathematics education apps that purport to portray maths learning as a fun experience. We accomplish this critique through the creation of a digital artwork called Arithmomania . This artwork challenges how users interact with education apps by employing the aesthetic of the glitch, an aesthetic characterized by reifying disorder and malfunction. Arithmomania shows fun as a miasma to learning, rather than the nostrum it is believed to be.